Respostas
respondido por:
2
Resolver através da fórmula de Bháskara!
a= x²
b= -11,2x
c= 21,75
x=-b+-√b²-4ac/2a
x= -(-11,2) +-√(11,2)² -4(1)(21,75)/2.1
x= 11,2 +-√125,44 - 87 / 2
x= 11,2 +- √38,44 / 2
x= 11,2 +- 6,2 / 2
x¹ = 11,2+6/2 = 17,4/2 = 8,7 x¹ = 8,7
x² = 11,2-6,2 = 5/2 = 2,5 x² = 2,5
a= x²
b= -11,2x
c= 21,75
x=-b+-√b²-4ac/2a
x= -(-11,2) +-√(11,2)² -4(1)(21,75)/2.1
x= 11,2 +-√125,44 - 87 / 2
x= 11,2 +- √38,44 / 2
x= 11,2 +- 6,2 / 2
x¹ = 11,2+6/2 = 17,4/2 = 8,7 x¹ = 8,7
x² = 11,2-6,2 = 5/2 = 2,5 x² = 2,5
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás